Development of Multiple Emulsion of Andrographolide for Taste Masking - Pandey, Mr. Sharad Prakash (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The objective of this study was to develop and evaluate water-in-oil-in-water multiple emulsions for taste masking of andrographolide isolated from Andrographis paniculata leaves. Materials and Methods: Andrographolide (diterpenoid lactone) is the major active bitter glycoside and has been found to possess remarkable hepatoprotective activity. Andrographolide isolated was effectively entrapped into a multiple emulsion to facilitate the delivery of andrographolide in liver cells. Results and Discussion: This also improved its therapeutic efficacy during hepatic damage. Multiple emulsions prepared were stabilized using a combination of hydrophilic as well as hydrophobic surfactants in ratio of 4:1. This is significant in achieving stable multiple emulsions. Multiple emulsions prepared were of optimum globular size and drug content was found to be around 80%. Conclusion: This may be attributed to their enhanced bioavailability, taste masking, and sustained release as well as physicochemical stability which prolong the activity of andrographolide in the multiple emulsions, which could be safer and more effective.